Body expression in the cinematic film (Journal of the College of Basic Education, 2022)
The creator of the artistic work has the ability to choose his expressive sensory images to reach his goal, within his philosophical vision and references in analyzing and installing imaginary sensory images with the aesthetic composition of the body and its expressive creative connotations in order to give the sense of the visual form embodied in the visual achievement and give it various dimensions, including the realism of the body or Its strangeness is within the embodiment that the maker of the artwork seeks for in order to fit his tools and artistic vision and influence the sensory perceptions of the recipient. In order for the artistic image to be complete, there must be compatibility between them.